377 Complications of Pediatric Tethered Cord Release: Seattle Children's Hospital Experience. (1st April 2022) - Pan, James; Hauptman, Jason S.; Susarla, Srinivas; Ellenbogen, Richard G.; Lee, Amy; Browd, Samuel R.; Ojemann, Jeffrey G.
Abstract : INTRODUCTION: We describe six years of surgical experience at our pediatric neurosurgery center, with a wide variety of operative complexity and etiologies related to tethered cord syndrome. While complications are well-described, the risk of complications associated with complexity of the procedure needs further investigation. Based on our findings, we propose guidelines to minimize complications and give attention to certain high-risk groups of patients. METHODS: Medical records of children who underwent surgery for tethered cord release (CPT 63200) from July 2014 to December 2020 were retrospectively reviewed after approval by the Institutional Review Board at Seattle Children's Hospital. Data collected included demographics, surgical technique, follow-up, and complications. We defined surgeries as complex if they involved usage of any of the following: plastic surgeon assistance, drain placement, duraplasty, or operative laser. Univariate analysis and multivariate logistic regression were used to determine covariates that were protective or risk factors for development of complications. RESULTS: In 242 contiguous tethered cord operations (51.8% male, mean age 74.8 months), the overall complication rate of any type was 10.7% (3.45% simple, 17.46% complex). Median time until complication was 11 days. Complications were associated with usage of the operative laser, increasing hospital length of stay, and increasing operative time. Plastic surgery assistance (OR 0.357, 95% CI 0.197-0.647, p=0.0007) and placement of a drain (OR 0.314, 95% CI 0.134-0.739, p=0.008) for complex cases were protective against development of complications. CONCLUSION: Our complication rate is comparable to those of others (1-4). However, multivariate logistic regression analysis suggests that plastic surgery assistance and drain placement can be protective factors, and should be considered in complex tethered cord operations.